MicroRNA Alterations in the Brain and Body Fluids of Humans and Animal Prion Disease Models: Current Status and Perspectives - Kanata, Eirini; Thüne, Katrin; Xanthopoulos, Konstantinos; Ferrer, Isidre; Dafou, Dimitra; Zerr, Inga; Sklaviadis, Theodoros; Llorens, Franc (Frontiers in Aging Neuroscience, 2018)
Prion diseases are transmissible progressive neurodegenerative conditions characterized by rapid neuronal loss accompanied by a heterogeneous neuropathology, including spongiform degeneration, gliosis and protein aggregation. The pathogenic mechanisms and the origins of prion diseases remain unclear on the molecular level. Even though neurodegenerative diseases, including prion diseases, represent distinct entities, their pathogenesis shares a number of features including disturbed protein homeostasis, an overload of protein clearance pathways, the aggregation of pathological altered proteins, and the dysfunction and/or loss of specific neuronal populations. Recently, direct links have been established between neurodegenerative diseases and miRNA dysregulated patterns. miRNAs are a class of small non-coding RNAs involved in the fundamental post-transcriptional regulation of gene expression. Studies of miRNA alterations in the brain and body fluids in human prion diseases provide important insights into potential miRNA-associated disease mechanisms and biomarker candidates. miRNA alterations in prion disease models represent a unique tool to investigate the cause-consequence relationships of miRNA dysregulation in prion disease pathology, and to evaluate the use of miRNAs in diagnosis as biomarkers. Here, we provide an overview of studies on miRNA alterations in human prion diseases and relevant disease models, in relation to pertinent studies on other neurodegenerative diseases.